Post‐thrombotic syndrome: a clinical review. Issue 5 (15th May 2013) - Baldwin, M. J.; Moore, H. M.; Rudarakanchana, N.; Gohel, M.; Davies, A. H.
Summary Up to half of patients with proximal deep vein thrombosis (DVT) will develop post‐thrombotic syndrome (PTS) despite optimal anticoagulant therapy. PTS significantly impacts upon quality of life and has major health‐economic implications. This narrative review describes the pathophysiology, risk factors, and diagnosis, prevention and treatment of PTS, to improve our understanding of the disease and guide treatment. Relevant articles were identified through systematic searches of the PubMed, EMBASE and Cochrane databases between 1966 and November 2011. Studies were included for detailed assessment if they met the following criteria: published in English, human study participants, study population aged > 18 years, and lower limb post‐thrombotic syndrome. All non‐systematic reviews and single patient case reports were excluded. Recurrent thrombosis, thrombus location and obesity are major risk factors, whereas the importance of gender and age remain uncertain. The diagnosis of PTS is based on clinical findings in patients with a known history of DVT. Several clinical scales have been described, with the Villalta Score gaining increasing popularity. Adequate anticoagulation and use of elastic compression stockings (ECS) following DVT can reduce the incidence of PTS. Catheter‐directed thrombolysis and mechanical thrombectomy of acute DVT may preserve valvular function. Studies to date of these techniques are encouraging, and have reported improved hemodynamics and a reduced incidence of PTS. The management of established PTS is challenging. Compression therapy, aimed at reducing the underling venous hypertension, remains the mainstay of treatment. This is despite a paucity of high‐quality evidence to support its use. Pharmacologic and surgical treatments have also been described, with a number of studies citing symptomatic improvement.